2019
DOI: 10.1016/j.mmcr.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Magnusiomyces clavatus infection in a child after allogeneic hematotopoetic stem cell transplantation: Diagnostic and therapeutic implications

Abstract: Magnusiomyces clavatus is an ascomycetous fungus causing invasive disease in immuno-compromised patients. Neutropenia, contaminated venous catheters, previous antifungal treatment are risk factors for this infection. We report a case of Magnusiomyces clavatus fungemia with pulmonary, renal and skin localizations in a 6-year-old boy with prolonged neutropenia because of three allogeneic hematopoietic stem cell transplantations. The infection was controlled by aggressive and strictly monitored combination therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Voriconazole and liposomal amphotericin B have provided mixed successes. Adding flucytosine to those drugs as suggested by Lacroix’s report and supported in vitro data could represent a potentially useful therapeutic modality for both (Tables 2–4) (Lacroix et al, 2007; Picard et al, 2014; Favre et al, 2016; Leoni et al, 2018; Liu et al, 2018). There are limited data about the therapeutic usefulness of posaconazole and isavuconazole (Miceli and Kauffman, 2015; Brunetti et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Voriconazole and liposomal amphotericin B have provided mixed successes. Adding flucytosine to those drugs as suggested by Lacroix’s report and supported in vitro data could represent a potentially useful therapeutic modality for both (Tables 2–4) (Lacroix et al, 2007; Picard et al, 2014; Favre et al, 2016; Leoni et al, 2018; Liu et al, 2018). There are limited data about the therapeutic usefulness of posaconazole and isavuconazole (Miceli and Kauffman, 2015; Brunetti et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…S. clavata is almost exclusively confined to systemic, life-threatening infections while the clinical presentation of infections caused by other arthroconidial fungi range from superficial ( Trichosporon spp. ), mucosal ( Galactomyces candidus ), allergic ( Trichosporon pneumonitis) to systemic forms ( T. asahii, M. capitatus , and G. candidus ) (Girmenia et al, 2005; Henrich et al, 2009; Bonifaz et al, 2010; Vaux et al, 2014; de Almeida Júnior and Hennequin, 2016; Durán Graeff et al, 2017; Esposto et al, 2018; Leoni et al, 2018; Salgüero Fernández et al, 2018). AML is the leading underlying condition for systemic infections caused by S. clavata such as for other arthroconidial yeasts (Girmenia et al, 2005; Henrich et al, 2009; Camus et al, 2014; de Almeida Júnior and Hennequin, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous case reports have indicated that S. clavata was resistant to echinocandins and sensitive to voriconazole in [ 2 , 5 , 8 , 10 , 12 ]. In addition, voriconazole and/or liposomal amphotericin B treatments were reported as the most successful ones [ 8 , 9 , 14 , 20 ]. In the current report, S. clavata infection developed while the patient was receiving fluconazole treatment.…”
Section: Discussionmentioning
confidence: 99%